Pengaruh Pemberian Buah Kurma Ajwa (Phoenix dactilyfera L) terhadap Kadar Hormon Anti-Mullerian (AMH) dan Gambaran Klinis Perempuan Perimenopause - Farah Ekawati Mulyadi; Rosdiana Natsir; Nasrudin Andi Mappaware; Suryani As'ad; Andi Wardihan Sinrang; Liong Boy Kurniawan (JURNAL KESEHATAN REPRODUKSI, 2023)
Background: Perimenopause is clinically characterized by the appearance of various complaints such as disturbed menstrual cycles, vasomotor symptoms, and mood changes that have an impact on reduced quality of life. The decline in ovarian reserve is thought to be the beginning of this transition which eventually triggers hormonal changes. AMH is used as a marker of ovarian reserve and clinically as a predictive biomarker of menopause. Ajwa dates contain various phytochemicals that have potential to be used to protect primordial follicles from various damage while reducing perimenopause complaints.Objective: This study aimed to analyze the effect of consumption of ajwa dates on AMH levels and clinical features of perimenopausal women.Methods: This quasi-experimental study with a pre-post control design was carried out at RSIA Sitti Khadijah I Muhammadiyah Makassar, South Sulawesi, Indonesia, from May to October 2021. This study involved 44 perimenopausal subjects aged 42-48 years who were divided into 2 groups randomly (28 intervention groups, 16 control groups). AMH levels were checked by ELISA method while the clinical features was assessed by clinical examination.Results and Discussion: AMH levels in the intervention group decreased more slowly than the control group (0.37 ± 0.36 ng/ml vs 0.55 ± 0.19 ng/ml, p<0.05). Complaints of sleep disturbances, vaginal dryness, and mood changes were better in the intervention group (p<0.05), while complaints of irregular menstrual cycles and hot flushes were not significantly different in either control and intervention groups.Conclusion: AMH levels in the intervention group decreased more slowly than in the control group. The clinical features in the intervention group were better than the control group. Ajwa dates can be a good nutrition in improving the quality of life of perimenopausal women.Keywords: Anti-Mullerian Hormone (AMH); Clinical Features; Ajwa Dates; Perimenopause.